2008
DOI: 10.1007/s11230-007-9122-6
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Pseudanthobothrium hanseni Baer, 1956 and description of P. purtoni n. sp. (Cestoda: Tetraphyllidea) from different pairs of rajid skate hosts, with comments on the host-specificity of the genus in the northwest Atlantic

Abstract: During a parasitological survey of Leucoraja erinacea, L. ocellata, Malacoraja senta and Amblyraja radiata from Passamaquoddy Bay and waters surrounding the West Isles of the Bay of Fundy, NB, Canada, seven species of cestodes were recovered. Examination of these skates revealed the presence of two distinct species of Pseudanthobothrium Baer, 1956: one was retrieved from M. senta and A. radiata, identified as P. hanseni Baer, 1956 and redescribed herein; the other was retrieved from L. erinacea and L. ocellata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…Randhawa et al (2007) assessed the host specificity of Echeneibothrium vernetae Euzet, 1956, Pseudanthobothrium hanseni Baer, 1956, and Pseudanthobothrium purtoni (Randhawa et al, 2008) using anatomical observations and partial sequence data of a variable region (D2) from the large subunit ribosomal DNA (LSU). We established that adult specimens of all 3 species infect ecological pairs (McEachran et al, 1976) of rajid host species.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Randhawa et al (2007) assessed the host specificity of Echeneibothrium vernetae Euzet, 1956, Pseudanthobothrium hanseni Baer, 1956, and Pseudanthobothrium purtoni (Randhawa et al, 2008) using anatomical observations and partial sequence data of a variable region (D2) from the large subunit ribosomal DNA (LSU). We established that adult specimens of all 3 species infect ecological pairs (McEachran et al, 1976) of rajid host species.…”
mentioning
confidence: 99%
“…The specificity of tetraphyllideans has been attributed to: (1) morphological adaptations of the scolex to the host mucosa (Williams, 1960(Williams, , 1966(Williams, , 1968a(Williams, , 1968b; (2) physiological adaptations of hosts to the parasites, such as serum factors (McVicar and Fletcher, 1970); and (3) ecological factors, such as substrate preference and diet of the hosts (Randhawa et al, 2008). Williams (1960) described the spiral valve mucosa of 3 rajid species and 10 species of elasmobranchs (Williams, 1968a) and concluded that the differences in topography of the gut mucosa contribute to the observed specificity of tetraphyllidean cestodes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…PCR conditions were 948C for 3 min, 35 cycles of 948C for 1 min, 578C for 30 s, 728C for 2 min and a final extension of 728C for 7 min. The Rhodophyta specimens were amplified with the primer pair T01N and T13N (Randhawa et al 2008). These primers amplify approximately 1100 bp of the 5?…”
Section: Dna Sequencingmentioning
confidence: 99%